Changes in the Solid-, Liquid-, and Epithelium-Associated Bacterial Communities in the Rumen of Hu Lambs in Response to Dietary Urea Supplementation - Li, Zhipeng; Mu, Chunlong; Xu, Yixuan; Shen, Junshi; Zhu, Weiyun (Frontiers in Microbiology, 2020)
The rumen bacteria in the solid, liquid and epithelial fractions are distinct and play important roles in the degradation of urea nitrogen. However, the effects of urea on rumen bacteria from the three fractions remain unclear. In this study, forty-two Hu lambs were fed a total mixed ration based on concentrate and roughage (55:45, dry matter basis) and randomly assigned to one of three experimental diets: a basal diet with no urea (UC, 0 g/kg), a basal diet supplemented with low urea levels (LU, 10 g/kg DM), and a basal diet supplemented with high urea levels (HU, 30 g/kg DM). After an 11-week feeding trial, six animals from each treatment were harvested. Rumen metabolites levels were measured, and bacteria of the rumen solid, liquid, and epithelial fractions were examined based on 16S rRNA gene sequencing. Under urea supplementation, the concentrations of ammonia and butyrate in the rumen increased, whereas the concentration of propionate decreased. The population of total protozoa was the highest in the LU treatment. Prevotella 1 was the most abundant genus in all samples. The unclassified Muribaculaceae, bacteria within the families Lachnospiraceae and Ruminococcaceae, and Christensenellaceae R7 were abundant in the solid and liquid fractions. Butyrivibrio 2 and Treponema 2 were the abundant bacteria in the epithelial fraction. Principal coordinate analysis showed separation of the solid, liquid and epithelial bacteria regardless of diet, suggesting that rumen fraction had stronger influences on the bacterial community than did urea supplementation. However, the influences on the bacterial community differed among the three fractions. In the solid and liquid fractions, Succinivibrionaceae UCG 001 and Prevotella 1 showed decreased abundance with dietary urea supplementation, whereas the abundance of Oscillospira spp. was increased. Howardella spp. and Desulfobulbus spp. were higher in the epithelial fraction of the UC and LU treatments relative to HU treatment. Comparison of predictive function among in the rumen solid, liquid, and epithelial fractions among the three treatments also revealed differences. Collectively, these results reveal the change of the rumen bacterial community to dietary urea supplementation.